Battery failure analysis and characterization of failure types. Issue 3 (19th May 2022) - Berg, Sean
Abstract: This article is an introduction to lithium‐ion (Li‐ion) battery types, types of failures, and the forensic methods and techniques used to investigate the origin and cause to identify failure mechanisms. This article discusses common types of Li‐ion battery failure with a greater focus on the thermal runaway, which is a particularly dangerous and hazardous failure mode. Forensic methods and techniques that can be used to characterize battery failures will also be discussed. This is the first article in a six‐part series. The first article describes ways in which Li‐ion batteries can fail, followed by a discussion of challenges assessing the reliability of such a rapidly evolving technology in article two. The third article discusses potential mitigation strategies for BESS facilities, and the fourth article discusses the consequences of catastrophic failure in a BESS. Article five provides a review of available analytical approaches to evaluate existing structures and design new structures for protection from Li‐ion battery hazards. The final article is an overview of Li‐ion BESS failures and risk management considerations.